2015
DOI: 10.1089/apc.2014.0166
|View full text |Cite|
|
Sign up to set email alerts
|

Anal Human Papillomavirus (HPV) Prevalences and Factors Associated with Abnormal Anal Cytology in HIV-Infected Women in an Urban Cohort from Rio de Janeiro, Brazil

Abstract: Identifying factors, including human papillomavirus (HPV) genotypes, associated with abnormal anal cytology in HIV-infected women have implications for anal squamous cell cancer (SCC) prevention in HIV-infected women. Anal and cervical samples were collected for cytology, and tested for high-(HR-HPV) and low-risk HPV (LR-HPV) genotypes in a cross-sectional analysis of the IPEC Women's HIV Cohort (Rio de Janeiro, Brazil). Multivariate log-binomial regression models estimated prevalence ratios for factors associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 41 publications
0
27
2
2
Order By: Relevance
“…In our study, HIV+ patients presented an altered AC in 42.9% of cases, and the figure was 26.8% in HIV-women. Our result for the HIV+ patients differed from that reported from another Brazilian study performed by Cambou et al (2015), where 30.4% of HIV+ women presented alterations in AC cytology. The difference between the results is likely to be due to the restricted number of samples in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, HIV+ patients presented an altered AC in 42.9% of cases, and the figure was 26.8% in HIV-women. Our result for the HIV+ patients differed from that reported from another Brazilian study performed by Cambou et al (2015), where 30.4% of HIV+ women presented alterations in AC cytology. The difference between the results is likely to be due to the restricted number of samples in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Collected cells were initially prepared for conventional cytology by directly spreading cells onto a glass slide and immediately immersing the slide in absolute ethanol for fixation. Both anal and cervical cytology was classified according to the Bethesda system (2001) because the anus and cervix have similar histopathologic features (Poggio, 2011;Cambou et al, 2015) The cells remaining in the swab were then collected and immersed in a flask containing 20 mL ThinPrep ® (Hologic, Bedford, MA, USA) refrigerated solution. The samples were processed and analyzed at the Institute of Tropical Medicine of the University of São Paulo.…”
Section: Cytology Colposcopy Anoscopy and Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…However consistent with the findings of Hessol et al (17), in which women with lower CD4 cell counts were more likely to have detectable oncogenic and non-oncogenic HPV types, a low CD4 nadir was significantly associated with anal HPV detection in the present study. In a study by Cambou et al (32), a significant correlation between a low CD4 nadir and previous CD4 counts was detected, indicating an increased risk for anal dysplasia in HIV-infected women with a history of severe immune devastation. The increased prevalence of HPV infection in HIV-infected individuals seems to be associated with immunosuppression (33).…”
Section: Discussionmentioning
confidence: 94%
“…23, 24 Our study found a similar prevalence of anal and cervical HR-HPV infection, which is consistent with prior studies. 16, 25 …”
Section: Discussionmentioning
confidence: 99%